On Apprehending Aesthetic Objects - Blaustein, Leopold (Phainomena (Ljubljana), 2025)
The study concerns the main elements of the aesthetic experience of both ordinary objects (e.g., a sunset) as well as artworks (e.g., a painting, a sculpture). These experiences are described as intentional, thus as directed toward their objects. It is argued that aesthetic experiences depend on the kind of objects apprehended; one experiences static and dynamic objects differently. Generally, aesthetic experiences are essentially temporal and function to constitute their objects. The study differentiates reproducing (e.g., oil on canvas), imaginative (e.g., objects seen in a painting), and reproduced (e.g., a city depicted in a photograph) kinds of objects. The structure of, and relations between, these objects are to be examined, including the imaginative character of space and time, which are inherent to works of art.
Keywords: aesthetic experience; aesthetic object; estetska predmetnost; estetsko izkustvo; fantazija; imaginative world; imaginativni svet; mesta nedoločenosti; phantasy; spots of indeterminacy